Further chemical study on Avicennia alba Bl - Kim Chanh, Nguyen Thi; Nga, Vo Thi; Hoai Thu, Nguyen Thi; Kim Tuyen, Pham Nguyen; Phi Phung, Nguyen Kim (Vietnam Journal of Chemistry, 2014)
Three iridoid glucosides and a lignan glucoside were isolated from the dried leaves of Avicennia alba Bl. (Avicenniaceae), including geniposidic acid (1), a mixture of 2’-O-[(Z)-4’′’-methoxycinnamoyl]mussaenosidic acid (2), 2’-O-[(E)-4’′’-methoxycinnamoyl]mussaenosidic acid (3), and syringaresinol 4-O-b-D-glucopyranoside (4). Their chemical structures were elucidated by spectroscopic methods as well as compared with data in the literature. These substances were isolated for the first time from this genus. Keywords: Avicennia alba, iridoid, lignan.